PENGARUH PENGGUNAAN KRIB BAMBU TERHADAP PERUBAHAN PENAMPANG BATANG SINAMAR, KAB. 50 KOTA - Sari, Ridha; Yunita, Rini (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
A river is a natural channel which conduct water discharge that end up in to the sea. The channel and the morphology of a river would change from time to time caused by human ativities or even by nature. There are two things would occure in the river, erosion and sedimentation. In the river engineering activity, groyne built due to increase the stability of the river bank and to catch the sediment. Bamboo, that part of grass species, grows a lot by the river. The river bank is one of the best habitat for bamboo to grows. This research aims to find out how the bamboo groyne could effect the cross section of Batang Sinamar river, 50 Kota District. This research was carried out by implanted the bamboo groyne by Batang Sinamar river bank, and the river’s cross section was measured before and after the implantation. The results of the mesurements were analized by using HEC-RAS program application. The results of this study are expected to be solutions for development that is in harmony with nature, and also support the sustainable development.